A geometric index to differentiate abnormal from normal septal wall motion on cardiac MRI. (May 2015) - Secchi, Francesco; Resta, Elda Chiara; Giardino, Antonello; Di Leo, Giovanni; Bandera, Francesco; Guazzi, Marco; Sardanelli, Francesco
Background: The definition of abnormal septal wall motion (SWM) is usually performed on a subjective visual assessment with cardiac MR (CMR). Purpose: To quantify SWM using a geometric index and to compare this index to the visual inspection in patients with or without abnormal SWM. Material and Methods: Cine CMR images of 100 consecutive patients were retrospectively assessed for visual evaluation of SWM and calculation of a convexity septal index (CSI) on mid-ventricular short-axis images, defined as b / a ( a = minimal distance from anterior to posterior ventricular junctions; b = maximal distance from septum to a ), obtained in end-systole (ES) and end-diastole (ED). Cohen κ, Bland-Altman method, Kruskall-Wallis, Mann-Whitney U, Jonckheere-Terpstra, and Spearman statistics were used to compare the two methods. Results: At visual evaluation, 73 patients had normal SWM (group A), nine abnormal SWM at ES (group B), and 18 at ES and ED (group C). Median CSI for group A was significantly higher (ES = 0.23, ED = 0.25) than those for group B and C (0.10–0.15) ( P < 0.001). Inter-reader reproducibility of visual evaluation was high (κ = 0.841, P < 0.001) while that for CSI was 77%. Average time for visual analysis was 3 min, for quantitative analysis 4 min. Conclusion: CSI is a simple and reproducible way to quantify SWM. ED CSI seems to be sensitive in detecting abnormal SWM in patients with apparently normal SWM at visual evaluation.